Reinforcement positif : Teknik untuk Meningkatkan Academic Engagement Siswa pada Pandemi Covid-19 - Permata Sari; Ferisa Prasetyaning Utami; Agung Prasetyo; Ilham Khairi Siregar; Ryan Hidayat Rafiola (Kuras Institute, 2022)
Academic engagement is important for the smooth learning process. However, in fact the involvement of students in the learning process is minimal. This study aims to determine the effectiveness of positive reinforcement to increase student academic engagement. This study is a single case experimental design, with an A-B-A design research involving one student at Global Madani Junior High School who has low academic engagement. The instrument used in this intervention is an academic engagement rating scale based on the research of Schreiner & Louis. Analysis of the data used is statistical analysis and clinical analysis. The results showed a significant increase in academic engagement through positive reinforcement on scores at baseline A1, intervention, and baseline A2. Teachers and counselors can use various kinds of positive reinforcement to make students actively involved in the learning process.